Adductor injuries in the National Basketball Association: an analysis of return to play and player performance from 2010 to 2019. Issue 4 (1st October 2020) - Patel, Bhavik H.; Okoroha, Kelechi R.; Jildeh, Toufic R.; Lu, Yining; Baker, James D.; Nwachukwu, Benedict U.; Foster, Mitchell G.; Allen, Answorth A.; Forsythe, Brian
ABSTRACT: Objectives : 1) To evaluate return to play (RTP) timing in National Basketball Association (NBA) athletes following adductor injuries, and 2) to evaluate the effect of adductor injuries on player performance, game availability, and career longevity following RTP. Methods : Adductor injuries in NBA athletes from the 2009–2010 to 2018–2019 seasons were identified utilizing publicly available records via previously validated methodology. RTP time was calculated, and player performance and game availability were compared pre- vs. post-injury. Additionally, an injury-free control group matched for age, BMI, position, and experience was assembled to allow for comparisons in performance, availability, and career length. Results : In total, 79 adductor injuries across 65 NBA athletes were identified. The average injured player was 28.3 ± 4.0 years of age, and had 6.5 ± 4.2 seasons of NBA experience. Guards were injured more frequently than forwards or centers (49% vs 25% vs 25%, respectively). All players were able to RTP following first-time adductor injury after missing an average of 7.7 ± 9.8 games (median [IQR]: 4 [1–9]) and 16.9 ± 20.4 days (median [IQR]: 9 [3.5–20]). Twelve players (18.5%) suffered an adductor re-injury at a mean latency of 509.5 ± 503.9 days. Adductor injuries did not result in significant changes in any major statistical category (points, assists, rebounds, steals, blocks, turnovers, field goal percentage), player efficiency rating (PER), minutes/game, games/season, or a number of all-star selections (all P > 0.05) following RTP. Additionally, when compared to matched controls, no difference was found in pre- to post-injury change of PER, games/season, or minutes/game (all P > 0.05). Career longevity was not significantly different between groups (P = 0.44). Conclusion : Following adductor injury, NBA players returned to gameplay after missing an average of 16 to 17 days, or 7 to 8 games. Adductor injury did not affect player performance, nor game availability or career longevity.